Discovery and Characterization of Novel Esterases with Ethyl Carbamate-Hydrolyzing Activity - LIU Qingtao, ZHU Sibao, WANG Tianwen, LI Chuang, QIAN Senhe, ZHANG Wenqing, CHENG Fan, TIAN Shufang (Shipin Kexue)
In this study, four esterases (ES1, ES5, ES8 and ES9) with relatively high ethyl carbamate (EC)-hydrolyzing activity at both pH 4.5 and 7.0 were identified from the NCBI database, and their soluble expression in recombinant Escherichia coli was achieved. Then, the expressed enzymes were purified and characterized. The results showed that the optimal temperatures for ES1, ES5, ES8 and ES9 were 70, 70, 55 and 55 ℃, respectively. The optimum pH for ES1, ES5 and ES9 was alkaline, while that for ES8 was neutral. The stability of all four enzymes was significantly reduced at temperature higher than 45 ℃ or pH lower than 5. Their activity was strongly inhibited by Fe3+, Co2+, and Cu2+. In the presence of 10% (V/V) ethanol, ES1, ES5, ES8 and ES9 maintained 50.48%, 48.44%, 42.60%, and 33.59% of their activity, respectively. They maintained 24.09%, 20.41%, 16.11%, and 10.73% of their activity, respectively, at a NaCl concentration of 5%, respectively. Their Michaelis constant (Km) values toward EC at pH 4.5 were 210.7, 213.8, 256.2 and 127.2 mmol/L, respectively, and their catalytic constant/Michaelis constant (kcat/Km) ratios were 214.31, 203.20, 161.46 and 257.43 L/(mol·s), respectively. Structural analysis indicated that the narrow substrate channel of ES9 might affect the entry of EC, thus affecting its maximum reaction rate (Vmax) toward EC; the relatively high affinity of ES9 for EC might be attributed to the strong hydrogen bonding between them. The EC-degrading esterases had good ethanol tolerance, which not only enrich the EC-hydrolyzing enzyme library, but also provide a new method for controlling the EC content in traditional fermented foods with low alcohol content.